No place to shelter: ethnography of the homeless population in the COVID-19 pandemic - Hermes Candido de Paula; Donizete Vago Daher; Fabiana Ferreira Koopmans; Magda Guimarães de Araujo Faria; Patricia Ferraccioli Siqueira Lemos; Marcela de Abreu Moniz
ABSTRACT Objective: to analyze how homeless people live, in times of COVID-19 pandemic, in the city of Rio de Janeiro. Method: an ethnographic research that used interviews and observations and articles published in newspapers and magazines of great circulation, using domain analysis. Results: the results tell how the COVID-19 pandemic emerged for the homeless population. Isolation led to emptying the streets and reducing passers-by, damaging their ways of living and their survival tactics. Hunger, thirst, absence of places for bathing and for fulfilling physiological needs became part of their daily lives. Final considerations: given the impossibility of having a place to shelter, acquiring food and water and the limitations in carrying out preventive measures, care actions offered by managers to limit the virus to spread, even in this population, are ineffective.